Chromosome genomics uncovers plant genome organization and function - Zwyrtková, Jana; Šimková, Hana; Doležel, Jaroslav (Biotechnology advances, 2021)
The identification of causal genomic loci and their interactions underlying various traits in plants has been greatly aided by progress in understanding the organization of the nuclear genome. This provides clues to the responses of plants to environmental stimuli at the molecular level. Apart from other uses, these insights are needed to fully explore the potential of new breeding techniques that rely on genome editing. However, genome analysis and sequencing is not straightforward in the many agricultural crops and their wild relatives that possess large and complex genomes. Chromosome genomics streamlines this task by dissecting the genome to single chromosomes whose DNA is then used instead of nuclear DNA. This results in a massive and lossless reduction in DNA sample complexity, reduces the time and cost of the experiment, and simplifies data interpretation. Flow cytometric sorting of condensed mitotic chromosomes makes it possible to purify single chromosomes in large quantities, and as the DNA remains intact this process can be coupled successfully with many techniques in molecular biology and genomics. Since the first experiments with flow cytometric sorting in the late 1980s, numerous applications have been developed, and chromosome genomics has been having a significant impact in many areas of research, including the sequencing of complex genomes of important crops and gene cloning. This review discusses these applications, describes their contribution to advancements in plant genome analysis and gene cloning, and outlines future directions.
Keywords: Genome, Plant; Plants; genomika; Next-generation sequencing; Flow cytometry; chromozomy rostlin; šlechtění rostlin; Chromosome genomics; Genomics; Plant chromosome; genom rostlinný; Chromosomes, Plant; Plant Breeding; Molecular marker; rostliny; DNA library; Gene cloning; Chromosome flow sorting